IMPACT OF SALIVA pH ON ORAL HEALTH: A COMPREHENSIVE ANALYSIS - Supurna Pandit, Sanchit Pradhan, Mohnish Muchhal, Monika Singh, Anupriya Srivastava (South Eastern European Journal of Public Health, 2024)
Saliva pH plays a crucial role in oral health, influencing the balance of oral microbiota and the prevention of dental caries. A neutral pH supports beneficial bacteria, while acidic conditions can promote demineralization of enamel and increase the risk of cavities. Saliva also aids in neutralizing acids, providing a protective barrier against pathogens. Regular monitoring of saliva pH can be a valuable tool for assessing oral health status. Key factors affecting saliva pH include diet, hydration, and systemic health, underscoring the importance of maintaining an optimal pH for overall dental wellness.